An investigation into the nature of Contractor's All Risks insurance, with particular reference to civil engineering and building risks - Beeby, Ronald, Eugene (My University, 2015)
The prime goal of this project report is to investigate whether it is sensible for contractors to utilise the facilities offered by Contractor's All Risks (CAR) insurance; following an outline of the main characteristics of CAR, the approach adopted refers mainly to an investigation of accidents and losses that have occurred on civil engineering and building projects and relating these incidents to the cost of insurance of each project. Research for this investigation concentrates primarily on conclusions that become evident from analysing, on a worldwide basis, the number of losses Chat have occurred per site during the course of construction of various types of civil engineering structures (such as dams, tunnels, harbour works) and buildings (such as high rise office blocks). A statistical model for each kind of structure is then drawn in graphical for it to enable the reader to ascertain the appropriate minimum insurance premium (or rate) related to the minimum corresponding deductibles. Deductions made from these statistical models indicate that the premium rate and corresponding deductibles vary from high values for exposed risks such as dams and harbour works, to lower values for less exposed risks such as office buildings. In conclusion, the findings of this investigation indicate that due to the high number and high costs of losses, especially on exposed risks, Contractor's All Risks insurance is indeed not only viable, but highly recommended.